Enkephalin-immunoreactive cells in the mesencephalic tegmentum project to the optic tectum of the teleosts Salmo gairdneri and Salmo salar - Vecino, Elena; Ekström, Peter; Sharma, Sansar C. (Cell and Tissue Research, 1991)
Immunocytochemistry using antibodies against Met-enkephalin and Leu-enkephalin has demonstrated a group of large enkephalin-immunoreactive neurons in the nucleus of the rostral mesencephalic tegmentum (mRMT) of two teleost fish, Salmo gairdneri and Salmo salar. Injections of cobalt-lysine in the medial optic tectum retrogradely labeled the above group of tegmental neurons. Tegmental neurons were labeled only ipsilaterally to the injection site. This indicates that enkephalinergic neurons in the nRMT project to the optic tectum, and that at least some of the enkephalinergic axons observed in the optic tectum belong to a tegmento-tectal pathway. Comparable enkephalinergic pathways have been described in reptiles and birds, where pretectal-mesencephalic nuclei contribute to the enkephalin-containing fibers that project to the optic tectum.